a: \(P\left(0\right)=2\cdot0^4+3\cdot0^2+4=4\)
\(P\left(1\right)=2\cdot1^4+3\cdot1^2+4=2+3+4=9\)
\(P\left(-1\right)=2\cdot\left(-1\right)^4+3\cdot\left(-1\right)^2+4=9\)
\(P\left(2\right)=2\cdot2^4+3\cdot2^2+4=32+18+4=54\)
\(P\left(-2\right)=2\cdot\left(-2\right)^4+3\cdot\left(-2\right)^2+4=54\)
`P(0)=2.0^4+3.0^2+4=0+0+4=4`
`P(1)=2.1^4+3.1^2+4=2+3+4=9`
`P(-1)=2.(-1)^4+3.(-1)^2+4=2+3+4=9`
`P(2)=2.2^4+3.2^2+4=32+12+4=48`
`P(-2)=2.(-2)^4+3.(-2)^2+4=32+12+4=48`
`P([-2]/3)=2.([-2]/3)^4+3.([-2]/3)^2+4=32/81+4/3+4=464/81`